A psychometric assessment of a human resources practice measure for temporary agency workers - Sobral, Filipa (2019)
Studies have proposed and validated several measures that evaluate employee's perceptions of the human resources practices (HRP). However, given the changes occurring in the labor market, there is a need to develop a measure specially adapted to the contingent workers specific employment relationship. Thus, this study assesses an HRP system scale that was administered to temporary agency workers (TAW) to examine the scale's response process, internal structure and relation to other variables (i.e., affective commitment). The measure was administered to 4,551 Portuguese TAW. The Messick's validation framework (1995) was use and two sectors were compared. Descriptive analyses, scale reliabilities, item characteristics, exploratory, confirmatory, and multiple group analyses demonstrated that the measure had good psychometric properties. Moreover, there were positive correlations between the HRP scale and affective commitment. The results contribute to a better understanding of managing TAW's in agencies and client companies. HRP are a valuable method for "communicating" with these workers, who are then able to recognize and respond to the investment. This is the first study to develop and assess the psychometric properties of an HRP system measure for TAW and to cross-validate it with workers' affective commitment towards both companies that are involved in this employment relation.